Employment, Mobility, and Active Labor Market Programs - Peter Fredriksson; Per Johansson (Uppsala University, Department of Economics, 2003)
Using a unique micro panel data set we investigate whether active labor market programs improve employment prospects and increase mobility in the longer run. We consider two prototype programs: job creation programs and training programs. We find that both programs reduce the chances of finding a job substantially. Moreover, both programs are associated with a locking-in e.ect: the probability of finding a job outside the home region decreases after program participation. However, this e.ect appears to stem exclusively from the decrease in the overall job finding rate.
urn:nbn:se:uu:diva-4457
Keywords: C41; J61; J64; J68; 330; Subsidized employment; labor market training; program evaluation; employment; contracted mobility; Arbeitsmarktpolitik; Beschäftigungspolitik; Weiterbildung; Theorie